Melampaui Keuntungan: Model Pembelajaran Kewirausahaan Berbasis Blue Economy Dengan Nilai Pancasila - Muhammad Andy Purnama; Mohammad Syaifuddin; Mohamad Syahri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Sustainable development requires entrepreneurship education that not only develops business competencies but also promotes environmental responsibility and Pancasila values. However, entrepreneurship learning in schools remains predominantly oriented toward conventional economic approaches and has not optimally integrated Blue Economy principles. This study aimed to develop a Blue Economy-based entrepreneurship learning model integrated with Project-Based Learning (PjBL) to strengthen students' entrepreneurial competencies and sustainability awareness. The study employed a Research and Development (R&D) approach using the ADDIE model, followed by a quasi-experimental one-group pretest–posttest design to evaluate the effectiveness of the developed model. The participants consisted of 11 seventh-grade students at Qurrata A'yun Gadang Boarding Junior High School. Data were collected through expert validation, observation, interviews, questionnaires, and pretest–posttest assessments and analyzed using descriptive statistics and a paired-sample t-test. The results showed that the developed learning model was highly feasible, with teaching material and content validation scores of 95.75% and 95%, respectively. Statistical analysis indicated a significant improvement in students' entrepreneurial competencies after the implementation of the learning model (p < 0.05). These findings suggest that the proposed learning model provides an effective approach to integrating entrepreneurship education, sustainability principles, and Pancasila values within classroom learning.